The power of assessment for learning : twenty years of research and practice in UK and US classrooms - Heritage, Margaret; Harrison, Christine (Christine Ann) (Corwin, 2019)
Enrich, grow, and sustain AfL in your classroom. Twenty years after the publication of Inside the Black Box, the landmark review of formative classroom assessment, international education experts Christine Harrison and Margaret Heritage tackle assessment for learning (AfL) anew, with fresh insights gained from two decades of research, theory, and classroom practice. Packed with key AfL ideas and supports, vignettes that illustrate AfL in action, and practice-based evidence to enrich understanding of AfL from both the teacher's and the student's perspectives, this book is a 'sounding board' fo.